Method for rapidly characterizing rate capability of carbon negative electrode

By establishing a standard curve of Raman spectroscopy and magnification performance in carbon negative electrode materials, the problems of long cycle and complex operation of carbon negative electrode materials in the prior art are solved, and fast and accurate magnification performance evaluation and large-scale magnification type are achieved. Efficient screening of materials.

CN119413777AActive Publication Date: 2025-02-11HUNAN UNIV

Patent Information

Application Number
CN202411737439.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing methods for evaluating the rate performance of carbon anode materials of alkali metal ion batteries have long test cycles and complex operations.

Method used

By establishing a standard curve with the Raman spectrum and magnification performance of the carbon negative electrode material, the magnification performance of the carbon negative electrode is quickly evaluated and long-term magnification performance testing is avoided.

Benefits of technology

It realizes rapid, simple and accurate evaluation of the carbon negative electrode rate performance, and efficiently screens large-ratio carbon negative electrode materials, which is easy to operate and low-cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119413777A_ABST
    Figure CN119413777A_ABST
Patent Text Reader

Abstract

The invention discloses a method for rapidly characterizing the rate capability of a carbon negative electrode, and belongs to the technical field of analysis and detection. The method comprises the following steps: carrying out peak-splitting fitting on a first-order Raman spectrum of a carbon negative electrode material to obtain defect structure information; a fast charging standard curve is established by adopting the area ratio (ID4 / IG) of a defect peak (D4 peak) to an ideal graphite peak (G peak) and the rate capability of the carbon negative electrode, and the fast charging standard curve is used as a basis for detecting the unknown rate capability of the carbon negative electrode. According to the method, the standard curve is established on the basis of statistical data, the hard carbon diffusion coefficient is rechecked and verified, the detection result is more accurate, and the problems that an existing method for evaluating the carbon negative electrode material of the fast-charging type alkali metal ion (lithium / sodium / potassium) battery is long in evaluation period and complex in operation process are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of analysis and detection, and in particular relates to a method for quickly characterizing the rate performance of a carbon negative electrode. Background Art

[0002] The electrochemical properties of alkali metal (lithium / sodium / potassium) ion batteries depend largely on the negative electrode materials. As one of the most promising negative electrode materials, carbon negative electrode materials have the advantages of abundant sources, low cost, environmental friendliness, and high electronic conductivity. They have the most commercial prospects in lithium, sodium, and potassium ion batteries. Among them, disordered carbon materials, including soft carbon and hard carbon, are the most commonly used carbon negative electrode materials. They have large interlayer spacing, abundant defect sites, and a large number of micropores, which are conducive to the adsorption and diffusion of alkali metal ions. Studies have reported that the microstructure of the carbon negative electrode significantly affects the storage behavior of alkali metal ions, thus playing a decisive role in the reversible capacity. Studies have found that the adsorption / desorption of ions at the edges and surface defects of the material is relatively easy, and abundant defects and large interlayer spacing are conducive to the improvement of rate performance. Raman spectroscopy is a powerful means to characterize the degree of defects in carbon materials.

[0003] The basic electrochemical performance test of carbon negative electrode materials mainly includes cycle performance test and rate performance test, which can obtain the specific carbon negative electrode life, capacity, working voltage, and capacity under different current densities, but its characteristic is that the test cycle is long. It is worth noting that in actual use, it is necessary to develop a method that can quickly, simply and accurately evaluate the rate performance of carbon-based negative electrodes for sodium ion batteries, so as to achieve the purpose of efficiently screening high-rate hard carbon negative electrodes. Summary of the invention

[0004] The purpose of the present invention is to provide a method for quickly characterizing the rate performance of carbon negative electrodes, which solves the problems of long evaluation cycle and complex operation of existing methods for evaluating carbon negative electrode materials for alkali metal ion (lithium / sodium / potassium) batteries.

[0005] The present invention establishes a standard curve by combining the Raman spectrum of the carbon negative electrode material with the rate performance as a basis for detecting the unknown rate performance of the carbon negative electrode. The rate performance of the carbon negative electrode can be quickly evaluated without long-term rate performance testing or multiple structural parameter collection, and high-rate carbon negative electrode materials can be efficiently and quickly screened.

[0006] The present invention first establishes a standard curve of carbon negative electrode rate performance, which mainly includes the following steps:

[0007] ① Test the rate performance of three or more carbon negative electrodes with different defect degrees at high current density and low current density, obtain the ratio of the reversible specific capacity at relatively high current density and the reversible specific capacity at relatively low current density, and obtain the rate capacity retention rate of three or more carbon negative electrodes with different defect degrees;

[0008] ② The three or more carbon anode powders with different defect degrees in step ① are subjected to Raman spectroscopy test to obtain Raman spectra, and first-order Raman spectrum peak fitting is performed to calculate the peak areas of the defect peak (D4 peak) and the ideal graphite peak (G peak), which are recorded as I D4 ,I G , and get I D4 / I G ratio;

[0009] ③ Establish a standard curve, using I in step ② D4 / I G The value is the horizontal axis, and the rate capacity retention rate obtained from the rate performance test in step ① is used as the vertical axis to establish a rate standard curve;

[0010] The second is the rate performance test of the sample to be tested:

[0011] The sample to be tested is subjected to Raman spectroscopy test to obtain the Raman spectrum, and the peaks are fitted to obtain I D4 / I G The value is used to calculate the rate performance of the sample to be tested using the standard curve in step (1) ③.

[0012] Preferably, the numerical range of the high current density and the low current density in step ① is 0.005A g -1 -10A g -1 .

[0013] Preferably, the value range of the high current density and the low current density in step ① is 20 mA g -1 -150mA g -1 .

[0014] Preferably, in step ①, the high current density is 60 mA g -1 , 90mA g -1 , 150mA g -1 One of the three, with a low current density of 20 mA g -1 .

[0015] Preferably, the carbon negative electrode is at least one of a hard carbon negative electrode, a soft carbon negative electrode, and a soft and hard carbon composite negative electrode.

[0016] Preferably, the hard carbon negative electrode is at least one of biomass-based hard carbon, resin-based hard carbon, and asphalt-based hard carbon.

[0017] Preferably, the carbon negative electrode is applied to one of lithium ion batteries, sodium ion batteries and potassium ion batteries.

[0018] Preferably, the laser wavelength of the Raman spectrum test in step ② and in the test sample test is one of 514nm, 532nm, and 633nm.

[0019] Preferably, the Raman spectroscopy test mainly includes the following steps:

[0020] (1) The Raman spectrum used ranges from 50 to 4000 cm -1 , laser power is 2-5mW;

[0021] (2) Perform a single-point scanning test, the number of scans may be, but not limited to, 3 times, each sampling point may be integrated 5 to 20 times, and the integration time may be 5 to 20 seconds;

[0022] (3) using origin data processing software to perform peak fitting, where the fitting function includes but is not limited to one of Gauss function, Gaussian function, Lorentz function, Voigt function, PsdVoigt1 function, and PsdVoigt1 function;

[0023] (4) Obtain the peak areas of different peaks in the first-order Raman spectrum of the carbon negative electrode and perform calculations.

[0024] Preferably, the rate performance test mainly includes the following steps:

[0025] (1) Preparation of electrode sheets:

[0026] The carbon negative electrode sample is mixed with a conductive agent and a binder in a certain proportion, wherein the active material content shall not be less than 80%. After being homogenized, it is coated on a copper foil current collector with a certain thickness. After vacuum drying at 60-100°C for 4-12 hours, it is cut into small discs with a diameter of 12 mm, thereby obtaining an electrode sheet. The active material loading in the electrode sheet is 1.5-7 mg cm -2 ;

[0027] (2) Battery assembly and rate performance testing:

[0028] In a glove box, a carbon negative electrode sheet is used as a working electrode to assemble into a half-cell, a full cell, or a three-electrode cell. The cell is left to stand for 6 to 48 hours, and the electrochemical rate performance is tested on a battery testing system.

[0029] The beneficial effects of the present invention are:

[0030] 1. This method is suitable for the rapid screening of carbon negative electrode materials for high-rate alkali metal ion (lithium / sodium / potassium) batteries. It can efficiently and accurately select negative electrode materials according to the needs of different application scenarios. It is simple to operate, fast to sample, safe and reliable, low-cost, and highly universal.

[0031] 2. The carbon negative electrode rate standard curve based on Raman spectroscopy in the present invention can obtain statistical data, making the established standard curve more accurate and improving the accuracy of detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 is a graph showing the relationship between the diffusion coefficient of the platform region and the rate performance in Example 1 of the present invention;

[0034] Figure 2 This is the Raman spectrum of the carbon negative electrode material in Example 1 of the present invention;

[0035] Figure 3 is the Raman spectrum fitting diagram of sample 1 in Example 1 of the present invention;

[0036] Figure 4 I in Example 1 of the present invention D4 / I G The relationship between the value (Raman laser wavelength is 532nm) and the diffusion coefficient of the platform area;

[0037] Figure 5 I in Example 1 of the present invention D4 / I G Standard curve of value (Raman laser wavelength is 532nm) and rate performance;

[0038] Figure 6 This is the Raman spectrum of the laser wavelengths of 532nm and 633nm in Example 2 of the present invention.

[0039] Figure 7 For Example 2 of the present invention, D4 / I G The relationship between the value (Raman laser wavelength is 633nm) and the rate performance;

[0040] Figure 8 For the comparative example 2 of the present invention, D1 / I G The relationship between the value (Raman laser wavelength is 532nm) and the rate performance;

[0041] Fig. 9 For the comparative example 3 of the present invention, D2 / I G The relationship between the value (Raman laser wavelength is 532nm) and the rate performance;

[0042] Fig.10 For the comparative example 4 of the present invention, D3 / I GThe relationship between the value (Raman laser wavelength is 532nm) and the rate performance. DETAILED DESCRIPTION

[0043] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0044] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only. Several improvements and modifications may be made without departing from the principles of the embodiments of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.

[0045] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0046] Example 1

[0047] In this embodiment, the Raman spectrum of the carbon negative electrode material is tested and mathematically fitted to predict the rate performance of the carbon negative electrode, which specifically includes the following steps:

[0048] 1. Establishing a standard curve for evaluating rate performance using Raman spectroscopy

[0049] 1. Pole preparation and battery assembly:

[0050] (1) Preparation of electrode sheets:

[0051] The carbon negative electrode sample, conductive carbon black, sodium carboxymethyl cellulose, and styrene butadiene rubber with a concentration of 48% were mixed in a mass ratio of 94%: 1.5%: 2.5%: 2%, and an appropriate amount of deionized water was added and stirred evenly to prepare a slurry. The slurry was coated on a copper foil current collector with a certain thickness, vacuum dried at 80°C for 12 hours, and then cut into small discs with a diameter of 12 mm, thereby obtaining an electrode sheet, and the active material loading in the electrode sheet was 5-7 mg cm -2 ;

[0052] (2) CR2032 button battery assembly:

[0053] In the glove box, the carbon negative electrode sheet was placed in the middle of the positive electrode shell with the active material side facing up, and 60 μL of electrolyte (1 mol L -1Ethylene carbonate / diethyl carbonate solution of sodium hexafluorophosphate (solvent volume ratio of 1:1), place a glass fiber separator, then add 60μL of electrolyte, place the sodium sheet, gasket, spring sheet, and negative electrode shell in sequence, and finally press the various parts of the battery into a whole with a pressure of 10Gpa to complete the assembly of the battery;

[0054] 2. Rate performance test:

[0055] The battery assembled in step 1 was left to stand for 8 hours, and the rate performance test was performed on the Xinwei battery test system or the Blue Power battery test system to obtain the rate performance of the carbon negative electrode. The current density was: 20 mA g -1 , 60mA g -1 , 90mA g -1 , 150mAg -1 , through a high current density (60mA g -1 , 90mA g -1 , 150mA g -1 ) and low current density (20 mA g -1 ) is used as the rate capacity retention rate to describe the quality of the rate performance, and is named according to the corresponding current density. The results are shown in Table 1.

[0056] 3. Constant current gap titration technology test:

[0057] The battery in step 1 was titrated using a constant current intermittent titration technique to study the Na + The pulse current applied during the test was 10 mA g -1 , the pulse time is 15min, the relaxation time is 1h, and the diffusion coefficient in the platform region (<0.1V) of the electrochemical curve is calculated. The results are shown in Table 1.

[0058] 4. Take the diffusion coefficient of the platform region obtained in step 3 as the horizontal axis and the 60 mA g obtained in step 2 as the horizontal axis. -1 The rate capacity retention rate under current density is used as the ordinate to establish a linear relationship, and the Pearson correlation coefficient is 0.81, indicating that the rate performance is highly positively correlated with the diffusion coefficient in the platform region. The results are shown in Table 3 and Figure 1 shown.

[0059] 5. Raman spectrum test with laser wavelength of 532nm:

[0060] (1) The carbon negative electrode material was detected by multi-site detection, with three point scans, and the Raman spectrum wave number range was 850 to 2000 cm -1 , laser power is 2mW;

[0061] (2) Perform a single-point scanning test, scan 3 to 5 times, integrate 15 times at each sampling point, and integrate for 3 seconds. The spectrum results are as follows: Figure 2 As shown;

[0062] (3) The first-order Raman spectra (850 to 2000 nm) were processed using origin data processing software. -1 The D peak and G peak of the wave number range are fitted separately, and the fitting function is Voigt function, and 5 peaks are obtained. The results are as follows Figure 3 As shown. From low to high Raman shift is ~1200cm -1 The D4 peak (sp 2 -sp 3 The stretching vibration of CC / C=C double bonds in hybrid structures or graphene terminal edges, A 1g Symmetrical), ~1350cm -1 The D1 peak at (defect-induced graphite, A 1g Symmetrical), ~1500cm -1 The D3 peak at (the short-range sp 3 Carbon), ~1580cm -1 The G peak at (ideal graphite lattice, E 2g Symmetrical), ~1620cm -1 D2 peak at (graphene layer on the surface of graphite lattice, E 2g Symmetrical), calculate the peak areas of the five peaks, and obtain the ratio of the D peak to the G peak area to obtain the corresponding defect degree information;

[0063] (4) Obtain the peak areas of different peaks in the first-order Raman spectrum of the carbon negative electrode, and calculate the peak areas of the D4 peak and the G peak, which are respectively recorded as I D4 ,I G , get I D4 / I G The ratios are shown in Table 2.

[0064] 6. Use I in step 5 D4 / I G The value was used as the horizontal axis, and the diffusion coefficient of the platform area in step 3 was used as the vertical axis to establish a linear relationship. The Pearson correlation coefficient was 0.84, indicating that the D4 peak was highly positively correlated with the diffusion coefficient of the platform area. The results are shown in Table 3 and Figure 4 shown.

[0065] 7. Establish a standard curve for evaluating the rate performance of carbon anode by Raman spectroscopy:

[0066] Take the Raman spectrum of step 5 as I D4 / I G The ratio is the horizontal axis, and the 60mA obtained by the rate test in step 2 -1 , 90mA g-1 , 150mAg -1 The rate capacity retention rate under current density was used as the ordinate, and a rate standard curve based on Raman spectrum with a laser wavelength of 532 was established. The results are shown in Table 4 and Figure 5 shown.

[0067] 2. Rate performance test of samples to be tested

[0068] 1. Perform Raman spectroscopy test on samples A and B in step 1, fit the peaks, and obtain I D4 / I G The values ​​are 0.38 and 0.46, respectively, as shown in Table 5;

[0069] 2. Use the Raman spectrum magnification standard curve in step 1 to calculate the sample A at 60mAg -1 、90mAg -1 , 150mAg -1 The capacity retention rates at the lower rates are 27.47%, 22.41%, and 18.45%, respectively. Sample B at 60 mAg -1 、90mAg -1 , 150mA g -1 The capacity retention rates at the lower rates are 30.66%, 24.83%, and 20.56%, respectively, as shown in Table 5.

[0070] Example 2

[0071] As the wavelength increases, the laser excitation energy decreases, and the area of ​​the D peak increases relative to the area of ​​the G peak. Figure 6 Therefore, this embodiment uses Raman spectroscopy testing with a laser wavelength of 633 nm, single-point scanning, 3 to 5 scans, 10 integrations for each sampling point, and an integration time of 10 seconds.

[0072] The same method as in Example 1 was used to characterize the Raman spectrum, make the pole piece, assemble the button battery, and perform the rate test under the same conditions. D4 / I G The value is the horizontal axis, and the 60mAg obtained by the rate test -1 , 90mA g -1 , 150mA g -1 The rate capacity retention rate under current density is used as the ordinate to establish a linear relationship. The results are shown in Table 4 and Figure 7 As shown, it shows that the I obtained based on the Raman spectrum with a laser wavelength of 633nm D4 / I G The value is highly positively correlated with the rate performance.

[0073] Comparative Example 1

[0074] In this comparative example, samples A and B were selected to be made into negative electrode sheets, and then assembled into button batteries to test the rate performance. The test results showed that sample A -1 , 90mA g -1 , 150mA g -1 The capacity retention rates at the lower rate are 27.19%, 21.86%, and 18.37%, respectively. Sample B at 60 mA g -1 , 90mA g -1 , 150mA g -1 The capacity retention rates at the lower rates are 30.52%, 24.87% and 20.33%, respectively, as shown in Table 6.

[0075] Comparative Example 2

[0076] This comparative example uses the same method as in Example 1 to characterize the Raman spectrum, make the pole piece, assemble the button cell, and conduct electrochemical tests under the same conditions. D1 / I G The peak area ratio is the horizontal axis, and the 60mA g -1 The rate capacity retention rate under current density is used as the ordinate to establish a linear relationship, and the Pearson correlation coefficient is 0.56. The results are shown in Table 4 and Figure 8 shown.

[0077] Comparative Example 3

[0078] This comparative example uses the same method as in Example 1 to characterize the Raman spectrum, make the pole piece, assemble the button cell, and conduct electrochemical tests under the same conditions. D2 / I G The peak area ratio is the horizontal axis, and the 60mAg obtained by the rate test -1 The rate capacity retention rate under current density was used as the ordinate to establish a linear relationship with a Pearson correlation coefficient of 0.50. The results are shown in Table 4 and Fig. 9 shown.

[0079] Comparative Example 4

[0080] This comparative example uses the same method as in Example 1 to characterize the Raman spectrum, make the pole piece, assemble the button cell, and conduct electrochemical tests under the same conditions. D3 / I G The peak area ratio is the horizontal axis, and the 60mAg obtained by the rate test -1 The rate capacity retention rate under current density is used as the ordinate to establish a linear relationship, and the Pearson correlation coefficient is 0.64. The results are shown in Table 4 and Fig.10 shown.

[0081] Table 1 Rate performance and platform diffusion coefficient results of carbon anode materials

[0082]

[0083] Table 2 I obtained by fitting the Raman spectra at different laser wavelengths D4 / I G value

[0084] <![CDATA[I D4 / I G (532nm)]]> <![CDATA[I D4 / I G (633nm)]]> Sample 1 0.39 1.05 Sample 2 0.44 1.27 Sample 3 0.32 0.99 Sample 4 0.32 0.92 Sample 5 0.21 0.55 Sample 6 0.58 1.44 Sample 7 0.45 1.01 Sample 8 0.31 0.93 Sample 9 0.44 1.31

[0085] Table 3 Correlation between diffusion coefficient and magnification, I D4 / I G Correlation between the value and the diffusion coefficient

[0086] Pearson correlation coefficient Diffusion coefficient and rate 0.81 <![CDATA[I D4 / I G Value and diffusion coefficient]]> 0.84

[0087] Table 4I D4 / I G ,I D1 / I G ,I D2 / I G ,I D3 / I G Correlation between the values ​​and rate performance

[0088]

[0089] Table 5 I of the samples to be tested D4 / I G Value, rate performance obtained by standard curve

[0090] <![CDATA[I D4 / I G ]]> <![CDATA[60mA g -1 ]]> <![CDATA[90mA g -1 ]]> <![CDATA[150mA g -1 ]]> Sample A 0.38 27.47% 22.41% 18.45% Sample B 0.46 30.66% 24.83% 20.56%

[0091] Table 6 Rate performance of the samples tested obtained by rate test

[0092] <![CDATA[60mA g -1 ]]> <![CDATA[90mA g -1 ]]> <![CDATA[150mAg -1 ]]> Sample A 27.19% 21.86% 18.37% Sample B 30.52% 24.87% 20.33%

[0093] In summary, the present invention uses the Raman spectrum of the carbon negative electrode material D4 / I GThe value and rate performance are used to establish a standard curve as a basis for detecting the unknown rate performance of the carbon negative electrode. This method can quickly evaluate the rate performance of the carbon negative electrode without undergoing a long period of rate performance testing and complex characterization of multiple microstructures. It can be found from Examples 1-2 and Comparative Examples 1-4 that the type and degree of defect structure represented by the D4 peak in the Raman spectrum are positively correlated with the diffusion speed of sodium ions in the carbon negative electrode, and the size of the diffusion coefficient affects the quality of the rate performance. Therefore, the degree of defect of the carbon negative electrode obtained by Raman spectroscopy can quickly evaluate the rate performance of the carbon negative electrode, and can efficiently, quickly and accurately screen large-rate carbon negative electrodes. At the same time, this method establishes a standard curve based on statistically significant data, showing the advantages of simple operation, rapid sampling, safety and reliability, low cost, accurate results, and strong universality, and is suitable for Raman with different laser wavelengths.

[0094] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for rapidly characterizing the rate performance of a carbon negative electrode, characterized in that: The following steps are involved: (1) The establishment of the standard curve of carbon negative electrode rate performance mainly includes the following steps: ① Test the rate performance of three or more carbon negative electrodes with different defect degrees at high current density and low current density, obtain the ratio of the reversible specific capacity at relatively high current density and the reversible specific capacity at relatively low current density, and obtain the rate capacity retention rate of three or more carbon negative electrodes with different defect degrees; ② The three or more carbon anode powders with different defect degrees in step ① are subjected to Raman spectroscopy test to obtain Raman spectra, and first-order Raman spectrum peak fitting is performed to calculate the peak areas of the defect peak (D4 peak) and the ideal graphite peak (G peak), which are recorded as I D4 ,I G , and get I D4 / I G ratio; ③ Establish a standard curve, using I in step ② D4 / I G The value is the horizontal axis, and the rate capacity retention rate obtained from the rate performance test in step ① is used as the vertical axis to establish a rate standard curve; (2) Rate performance test of the sample to be tested The sample to be tested is subjected to Raman spectroscopy test to obtain the Raman spectrum, and the peaks are fitted to obtain I D4 / I G The value is used to calculate the rate performance of the sample to be tested using the standard curve in step (1) ③.

2. A method for rapidly characterizing the rate performance of a carbon negative electrode according to claim 1, characterized in that: The numerical range of the high current density and the low current density is 0.005A g -1 -10A g -1 .

3. A method for rapidly characterizing the rate performance of a carbon negative electrode according to claim 1 or 2, characterized in that: The high current density and low current density values ​​range from 20 mA g -1 -150mA g -1 .

4. A method for rapidly characterizing the rate performance of a carbon negative electrode according to claim 1 or 2, characterized in that: The high current density is 60 mA g -1 , 90mA g -1 , 150mA g -1 One of the three, with a low current density of 20 mA g -1 .

5. A method for rapidly characterizing the rate performance of a carbon negative electrode according to claim 1 or 2, characterized in that: The carbon negative electrode is at least one of a hard carbon negative electrode, a soft carbon negative electrode, and a soft and hard carbon composite negative electrode.

6. A method for rapidly characterizing the rate performance of a carbon negative electrode according to claim 5, characterized in that: The hard carbon negative electrode is at least one of biomass-based hard carbon, resin-based hard carbon, and asphalt-based hard carbon.

7. A method for rapidly characterizing the rate performance of a carbon negative electrode according to claim 1 or 2, characterized in that: The carbon negative electrode is applied to one of lithium ion batteries, sodium ion batteries and potassium ion batteries.

8. A method for rapidly characterizing the rate performance of a carbon negative electrode according to claim 1 or 2, characterized in that: The laser wavelength of the Raman spectrum test is one of 514nm, 532nm and 633nm.

9. A method for rapidly characterizing the rate performance of a carbon negative electrode according to claim 1 or 2, characterized in that: The Raman spectroscopy test mainly includes the following steps: (1) The Raman spectrum used ranges from 50 to 4000 cm -1 , laser power is 2-5mW; (2) Perform a single-point scanning test, the number of scans may be, but not limited to, 3 times, each sampling point may be integrated 5 to 20 times, and the integration time may be 5 to 20 seconds; (3) using origin data processing software to perform peak fitting, where the fitting function includes but is not limited to one of Gauss function, Gaussian function, Lorentz function, Voigt function, PsdVoigt1 function, and PsdVoigt1 function; (4) Obtain the peak areas of different peaks in the first-order Raman spectrum of the carbon negative electrode and perform calculations.

10. A method for rapidly characterizing the rate performance of a carbon negative electrode according to any one of claims 1 or 2, characterized in that The rate performance test mainly includes the following steps: (1) Preparation of electrode sheets: The carbon negative electrode sample is mixed with a conductive agent and a binder in a certain proportion, wherein the active material content shall not be less than 80%. After being homogenized, it is coated on a copper foil current collector with a certain thickness. After vacuum drying at 60-100°C for 4-12 hours, it is cut into small discs with a diameter of 12 mm, thereby obtaining an electrode sheet. The active material loading in the electrode sheet is 1.5-7 mg cm -2 ; (2) Battery assembly and rate performance testing: In a glove box, a carbon negative electrode sheet is used as a working electrode to assemble into a half-cell, a full cell, or a three-electrode cell. The cell is left to stand for 6 to 48 hours, and the electrochemical rate performance is tested on a battery testing system.

Citation Information

Patent Citations

  • Secondary battery and electric device

    CN116387446A

  • Lithium battery material thermal stability detection method

    CN118294437A

  • Hard carbon negative electrode material and pressure resistance screening method thereof

    CN118522895A

  • Performance evaluation method and system for porous carbon material of negative electrode of lithium ion battery

    CN118624838A

  • Quality management method for negative electrode active material of lithium-ion secondary battery, method of manufacturing negative electrode of lithium-ion secondary battery, method of manufacturing lithium-ion secondary battery, negative electrode of lithium-ion secondary battery, and lithium-ion secondary battery

    US20150300956A1

Cited By

  • Evaluation method for rate capability of sodium ion battery hard carbon material

    CN120820603A